2012
DOI: 10.1002/pon.3132
|View full text |Cite
|
Sign up to set email alerts
|

Post‐traumatic stress symptoms among mothers of children with leukemia undergoing treatment: a longitudinal study

Abstract: Specific psychological interventions could be devised for mothers at risk for short and long-term PTSS just after the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 46 publications
3
35
0
1
Order By: Relevance
“…One study found that lower education was associated with higher depression scores and PTSS up to 1 year post‐diagnosis (Demirtepe‐Saygili & Bozo ; Tremolada et al . ). Notably, family income was not associated with distress (Klassen et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…One study found that lower education was associated with higher depression scores and PTSS up to 1 year post‐diagnosis (Demirtepe‐Saygili & Bozo ; Tremolada et al . ). Notably, family income was not associated with distress (Klassen et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Tremolada et al . ). Tumour relapse was also as a significant predictor for the prevalence of traumatic stress, with traumatic stress nearly doubling following relapse (Jurbergs et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Variability in the experience of closeness has been proposed to reflect baseline differences across families or differences in the illness and treatment challenges faced by couples . The 1 quantitative study of couple's closeness indicated that female partners reported a significant increase in emotional closeness with their partners from diagnosis to 1 year postdiagnosis …”
Section: Resultsmentioning
confidence: 99%
“…There are a variety of factors that were not evaluated in this review, such as the influence of health status and lifestyle (metabolic syndromes, chronic conditions, nutritional status, symptoms management, physical activity and psychological well-being)(Badr et al,2013; Brinkman et al,2013; Hartman et al,2013; Huang et al,2013; Tonorezos et al,2013), environmental factors (coping strategies, education and psychological status of family members)(Norberg and Boman,2008; Trask et al,2009; Tremolada et al,2013; Long et al,2014; Williams et al,2014; Williams and McCarthy,2014 ) and the interaction between chemotherapy and other supportive care drugs that may exert additive neurotoxic effects (antibiotics, antifungals and neuropsychiatric drugs)(Haidar and Jeha,2011; van Schie et al,2011; Barrett et al,2013; Ruggiero et al,2013). A multidisciplinary approach is needed to ascertain the impact of contemporary ALL treatments on these adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%